2016
DOI: 10.1002/jor.23398
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the articular cartilage T and T2 relaxation times changes after ACL reconstruction in injured and contralateral knees and relationships with bone shape

Abstract: The objectives of this study were twofold: (1) to evaluate the longitudinal change in cartilage T and T 6- and 12-months after ACL reconstruction (ACLR) in both reconstructed and intact contralateral knees with the aim of validating the role of the contralateral knee as an internal control in longitudinal studies; (2) to explore relationships between bone shape at the time of injury and the progression of T and T over 12-months after ACLR. T and T cartilage relaxation times and 3D MRI-based statistical shape m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 47 publications
5
68
0
Order By: Relevance
“…The diffuse nature of 18 F-NaF uptake may be due to changes in joint loading, knee rehabilitation or other factors that affect the whole-joint. Diffuse increases in cartilage T 2 and T 1ρ relaxation times have also been observed after ACL tears 23 . High uptake is also often seen surrounding the ACL graft sites, likely as a result from the ACL reconstruction surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The diffuse nature of 18 F-NaF uptake may be due to changes in joint loading, knee rehabilitation or other factors that affect the whole-joint. Diffuse increases in cartilage T 2 and T 1ρ relaxation times have also been observed after ACL tears 23 . High uptake is also often seen surrounding the ACL graft sites, likely as a result from the ACL reconstruction surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, this study used the contralateral knee as a control instead of age-matched healthy subjects. Other studies have shown that following ACL injury, the contralateral knee may also show changes due to changes in loading, knee biomechanics, or other factors 23 . However, we felt that in this study, the contralateral knee serves as the ideal control as it minimizes inter-subject variation; in particular, that intra-subject tracer distribution would be equivalent to both knees for comparison of PET SUV.…”
Section: Discussionmentioning
confidence: 99%
“…All the segmentations underwent a strict protocol of quality control and a single user (GI) manually adjusted the bone segmentation in case of failure of the automatic procedure. 3D-SSM was performed as previously described and evaluated [35, 36]. …”
Section: Methodsmentioning
confidence: 99%
“…Elevations in this lateral region have also been observed as predictors of the changes in patientreported outcomes 12 months after reconstruction (16). Longitudinal T 1ρ progression in both injured and contralateral knees has been observed as soon as 6 months after ACL reconstruction, specifically in medial and lateral femur and femoral trochlea compartments (17).…”
Section: Introductionmentioning
confidence: 98%